2022
DOI: 10.3389/fendo.2022.1039051
|View full text |Cite
|
Sign up to set email alerts
|

Secular increase in the prevalence of gestational diabetes and its associated adverse pregnancy outcomes from 2014 to 2021 in Hebei province, China

Abstract: ObjectiveWe aimed to investigate the secular prevalence of gestational diabetes mellitus (GDM) and evaluate its adverse pregnancy outcomes among pregnant women in Hebei province, China.MethodsWe analyzed the data from the monitoring information management system for pregnant women in 22 hospitals of Hebei province, China. In this study, 366,212 individuals with singleton live births from 2014 to 2021 were included, of whom 25,995 were diagnosed with gestational diabetes. We described the incidence of common co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The risk of GDM in AMA women increased. Previous studies [ 27 29 ] showed that the risk of GDM pregnant women delivering macrosomia and LGA infants was significantly higher than that of non-GDM pregnant women. This could also be related to the fact that AMA mothers pay increased attention to nutritional supplementation during pregnancy, resulting in excessive nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of GDM in AMA women increased. Previous studies [ 27 29 ] showed that the risk of GDM pregnant women delivering macrosomia and LGA infants was significantly higher than that of non-GDM pregnant women. This could also be related to the fact that AMA mothers pay increased attention to nutritional supplementation during pregnancy, resulting in excessive nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that women with GDM also experienced a higher risk of NICU admission. 24 , 25 Maternal hyperglycemia can lead to fetal hyperinsulinemia, promoting development of insulin-sensitive tissues (i.g., liver, fat, and muscle) but not non-insulin-sensitive tissues (i.g., brain and kidney). 26 The imbalance development of different fetal tissues may lead to poor tolerance to hypoxia in utero and poor adaptability to the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study involving 13 hospitals in China (including multiple pregnancies) showed an incidence of GDM of 17.5% (3002/17,186). 14 But the incidence of GDM varies a large rank in different areas of China, which was demonstrated a GDM incidence of 7.1% in Hebei Province, 15 while 21.00% of Ningbo City in Zhejiang Province and 21.76% of Peking City. 16 17 It is speculated that the possible reasons involve selection bias arising from single-center research.…”
Section: Discussionmentioning
confidence: 99%